Evaluation of properties of Trinidad Lake Asphalt and SBS-modified petroleum asphalt. (17th January 2019) - Xu, Song; Huang, Wei; Cai, Fuming; Huang, Heyao; Hu, Changbin
Abstract: The properties of Trinidad Lake Asphalt (TLA) and SBS compound modified petroleum asphalt were investigated. Results show that the compound of TLA and SBS exhibits a remarkable combined effect on enhancing the deformation resistance of asphalt, and SBS can offset partial negative effect of TLA on the creaking resistance of asphalt, which will extend the applicable area of TLAMPA. FTIR and TG curves indicate TLA and SBS are physically mixed into petroleum asphalt and have little influence on the thermal stability. TLA and SBS also exhibit combined effect on improving anti-aging performance of asphalt, which would extend the service life of pavement.